Pembuatan Sistem Perancang Peredam Kebisingan - Prasetya, Rahmat Bagus; Gunadi, Sunartoto; Wati, Erna Kusuma (Universitas Nurul Huda, 2020)
One of the problems experienced by the community, whether at home or at work, was the disruption in the sense of concentration caused by noise. This study aims to measure noise as well as provide materials to reduce noise in the area. The time for data collection was one day, carried out for 4 samples of data collection based on a reference from the Ministry of Environment, no: Kep-48 / MENLH / 11/1996. The measurement method also using SNI standard number 7231 in 2009. Then based on the noise value displayed on the instrument, material recommendations will be given based on the value of Noise Reduction Coefficient (NRC), Sound Transmission Coefficient (STC) and Loss Factor. The results of noise measurements at the AT-Taqwa Mosque are 77.1 dB and the recommended material recommended by the tool is Acourete Perfowood - Acoustic Panel 881 with NRC 0.375. While the measurement at the Musholla at Pasar Minggu station is 76.8 dB and the recommended material recommended by the tool is Accourete Fiber 300 with an NRC of 0.44.